2013
DOI: 10.1093/jjco/hyt053
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Intervention Trials for Colorectal Cancer

Abstract: There have been a number of candidates for chemopreventive agents from synthetic drugs and natural compounds suggested to prevent colorectal cancer. However, they have shown modest efficacy in humans. The reason for this could be partly explained by the use of inappropriate models in vitro and in vivo, and the limitation of chemoprevention trials. In Japan, there are no cancer chemopreventive medicines, and few cancer chemoprevention trials to date. In contrast, an increase in the prevalence of colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 81 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…Epidemiologic and retrospective studies have demonstrated that metformin which is an oral antidiabetic drug decreases incidence rate of colorectal cancer potentially (18). Although the patient took metformin for 15 years, it is difficult to confirm that metformin has played an important role in this regression.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic and retrospective studies have demonstrated that metformin which is an oral antidiabetic drug decreases incidence rate of colorectal cancer potentially (18). Although the patient took metformin for 15 years, it is difficult to confirm that metformin has played an important role in this regression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have revealed that both of the mRNA and protein expression of E-cadherin were upregulated with metformin-treated ESCC cells (data not shown). On the other hand, some meta-analyses also epidemiologically proved that metformin could reduce mortality and incidence rates of several cancers such as colorectal cancer and hepatocellular carcinoma [24]. Moreover, it is established that metformin shows high safety for nondiabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, NSAID antineoplastic effect may be also exerted through COX independent mechanisms, including other specific drug targets such as NF-KB, caspases, PDEs, survinin, protein kinases etc. [5,7,8,10] Indirect effect on COX has been also reported specifically for aspirin (besides inhibitory action) through the anti-platelet activity of the drug. [7] Therefore, NSAID chemopreventive mechanism is likely dual: some effects derived from the fundamental anti-inflammatory activity (through COX inhibition), while others appear to be unrelated to this propertysuppressing neoplasia through different pathways.…”
Section: Chemopreventive Mechanismmentioning
confidence: 93%
“…[10] Supportive Arguments (1-2 bleeds / 10.000 person-years) toxicity. [2,7] Regarding cardiovascular toxicity from selective COX-2 inhibitors, shorter treatment duration appears as a relatively safe (specifically for celecoxib administration in individuals with low cardiovascular risk) and potentially effective option[1, 3,5] (although the antineoplastic effect may attenuate and vanish soon after interruption of this particular treatment [7,8], likely being rather cytostatic than cytotoxic [5]). …”
Section: Chemopreventive Mechanismmentioning
confidence: 99%